Le projet TBM : un exemple de modalité de collaboration entre chercheurs et praticiens en Norvège - Claire Vaugelade Berg (Nantes Université, 2010)
This article offers both a description of the main characteristics of an ongoing research project in Norway and, through the presentation of an example, an illustration of the way developmental research is understood in this research. The project is rooted within a theoretical approach where the notions of co-learning and community of inquiry are central. Relevant issues emerging from this project are presented and discussed through this article, especially the relationship between knowledge arising from practice and knowledge arising from research.